Influência de ferro e de alumínio amorfos do solo na reatividade de quatro corretivos de acidez - GOMES, MARCO ANTONIO FERREIRA; RIBEIRO, ANTONIO CARLOS; COSTA, LIOVANDO MARCIANO DA; FILHO, WALDEMAR MOURA (Revista Ceres, 2015)
.